English distance learning difficulties in light of Corona pandemic from the perspective of primary school students in Alquwayiyah province - Alyabis, Sara Saad; Alruaithi, Eman Mohammed Ahmed (Journal of Educational and Psychological Sciences, 2023)
The study aimed to identify the English distance learning difficulties in light of Corona pandemic from the perspective of primary school students in Alquwayiyah province. To achieve the objectives of the study, the descriptive survey method was followed, where a questionnaire was used to collect data, which consisted of four main aspects for difficulties in learning skills (listening, speaking, reading, and writing). The study sample consisted of (367) students from the upper grades (fourth, fifth, sixth) of the elementary school. The most important findings of the study were as follows: Students of the upper grades of the elementary school in Alquwayiyah province facing difficulties in English distance learning difficulties in light of Corona pandemic, at a high degree, with a difficulty rate of 71.7%. The difficulties of learning the speaking skill ranked first with a difficulty of 74.9%, followed by the learning of writing skill which ranked second with a difficulty of 72.9%, then the learning of listening skill which ranked third with a difficulty of 70.8%, and finally the learning of the reading skill which ranked fourth with a difficulty of 68.2%. There are statistically significant differences between the difficulties of reading English skill in distance learning through Madrasati platform from the students' perspective due to the difference of the grade. There are no statistically significant differences between the difficulties of distance learning of the skills: listening, speaking, and writing in English through Madrasati platform from the students' perspective due to the difference of the grades. Also, there are no statistically significant differences between the difficulties of distance English language learning skills through Madrasati platform from the students' perspective due to previous experiences in learning English.
Keywords: Difficulties; English Language Curriculum; Distance Learning; Covid-19